Fixed Point Theorems and Convergence Theorems for a New Generalized Nonexpansive Mapping. (10th December 2018) - Donghan, Cai; Jie, Shi; Weiyi, Liu
Abstract: This paper introduces a new mapping that is weaker than nonexpansive mapping. The new mapping is different from the Suzuki's generalized nonexpansive mapping. This paper introduces a new iteration process for the fixed point, and gives fixed point theorems and Convergence theorems for a new generalized nonexpansive mapping in Banach space, insteading of uniformly convex Banach space.